Implementasi Nilai-nilai Religius pada Siswa Attention Deficit Hyperactivity Disorder (ADHD) di SD Negeri Pajang 1 Surakarta Tahun Ajaran 2016/2017 - Hastuti, Winda, Drs. H. Mulyadi Sri Kamulyan, S.H, M.Pd (2017)
The purposes of this study describe: 1) The values of religious instilled in students with ADHD in Primary Schools 1 Pajang of Surakarta, 2) Implementation of religious values in students with ADHD in Primary Schools 1 Pajang of Surakarta, 3) Identifying the obstacles encountered by teachers in implementation process of religious values in students with ADHD in Primary Schools 1 Pajang of Surakarta, 4) The solutions are adopted by the teacher to minimize obstacles in implementation process of religious values on ADHD in Primary Schools 1 Pajang of Surakarta. The method that used in this reseach is descriptive qualitative using case study design. Techniques of data collection are observation, interview and documentation. The validity of the uses triangulation of data sources and methods. The technique of data analysis of this research uses interactive qualitative analysis. The results of this research are: 1) The values instilled in students' religious ADHD in Primary Schools 1 Pajang of Surakarta include BTA as an extracurricular activities, planting, habituation of prayer according to religious learning (except islamic education by reciting Al Fatihah and prayer before learning), tolerant/in harmony with other faiths, saving money every day, teaching properties of prophet likes shidiq, amanah, tabligh, and fathonah, 2) Implementing religious values in students ADHD through habituation, integrating all subject of education, familiarization class policy, as well as exemplary, 3) Constraints that faced to the teachers in implementation religious values in students with ADHD is parenting parents less precise, communication with parents is difficult, and the constraints on students with ADHD (primarily emotional and attention is less focused), 4) Solution that undertaken by the teacher to minimize the constraint is understanding the condition of the students, in collaboration with the teacher assistant special, utilizing book liaison, establishing communication with the parents, facilitating students to answer questions, waiting to calm the students, as well as to communicate with the teacher for private lessons.